Plane-interface-induced lignin-based nanosheets and its reinforcing effect on styrene-butadiene rubber - C. Jiang; H. He; P. Yu; D. K. Wang; L. Zhou; D. M. Jia (eXPRESS Polymer Letters)
Lignin was viewed as a spherical microgel in aqueous alkali. While spread out in a monolayer or adsorbed on a surface, lignin was made up of flexible, disk-like molecules with approximately the same thickness of 2 nm. According to this principle, we employed the lamina of montmorillonite (MMT) as a plane template to anchor cationic lignin (CL) on its two sides, resulting in the formation of CL-MMT hybrid materials (CLM). The isotherm adsorption behavior and structure characteristics of CLM were studied. The results showed that CLM was individually dispersed nanosheets with a thickness of about 5 nm when the mass ratio of CL to MMT is more than 2:1 and prepared at acidic or neutral pH. Compared to the cocoagulation of lignin and styrene-butadiene rubber (SBR), CLM obviously accelerated the coagulation rate, due to the reduction of surface activity of CL restricted by MMT. The nanoscale dispersion of CLM in SBR matrix significantly improved the tensile strength of CLM/SBR nanocomposites to 14.1 MPa by adding only 10 phr CLM and cardanol glycidyl ether (CGE) as compatibilizer. Dynamic mechanical analysis (DMA) showed that the glass transition temperature of SBR/CLM nanocomposites decreased with increasing CLM loading. Correspondingly, a special interfacial structure was proposed.